Energy efficiency of manufacturing processes and systems - an introduction - Salonitis, Konstantinos (MDPI, 2020)
This Special Issue of Energies was devoted to the topic of “Energy Efficiency of Manufacturing Processes and Systems”. It attracted significant attention of scholars, practitioners, and policy-makers from all over the world. Eighteen papers on this topic were submitted between 2018 and 2020, and a total of 10 papers were published. Main topics included the energy efficiency improvement in both the manufacturing process and system levels. Furthermore, new methodologies and analysis approaches in developing energy efficiency were presented.
Keywords: digital manufacturing; sustainable manufacturing; clean manufacturing; manufacturing energy efficiency